1979
DOI: 10.1111/j.1471-0528.1979.tb10820.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maternally Administered Pethidine or Epidural Bupivacaine on the Fetus and Newborn

Abstract: Summary The continuous fetal heart rate pattern, condition of the baby at birth and its subsequent behaviour were compared in three groups of infants whose mothers received during labour either no drugs, intramuscular pethidine or epidural bupivacaine. The blood levels of pethidine and bupivacaine were measured at delivery in a maternal vein, and umbilical artery and vein, and in the newborn during the first 48 hours of life. The only significant changes in the fetal heart rate pattern occurred in association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…We found no significant difTerences at all in these groups and, if anything, the auditory and visual orientation in the group on pethidine alone were marginally better but this difference did not reach statistical significance. These observations parallel those of Tronick et al (1976) and Lieberman et al (1979).…”
Section: Discussionsupporting
confidence: 84%
“…We found no significant difTerences at all in these groups and, if anything, the auditory and visual orientation in the group on pethidine alone were marginally better but this difference did not reach statistical significance. These observations parallel those of Tronick et al (1976) and Lieberman et al (1979).…”
Section: Discussionsupporting
confidence: 84%
“…It is clear that the newborn may be at least transiently affected by anesthetics and analgesics administered during labor and delivery. 3,[33][34][35] For example, the use of opioids for labor analgesia is associated with neonatal respiratory depression. In contrast to these short-term effects, there are only few studies attempting to assess the effect of mode of delivery on long-term child neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping the above caveats in mind, the studies that were done using bupivacaine, which is the most common anesthetic used for labor epidurals at this time, have reported conflicting results with regard to neurobehavioral changes (82‐89). One study found neonates born to mothers with an epidural habituated and oriented better to inanimate auditory stimuli at 1 day of age (90).…”
Section: Fetal and Neonatal Effects Of Epidural Anesthesiamentioning
confidence: 99%